Imagens do poder: as fotografias da legalidade pelas lentes da assessoria de imprensa do governo do Estado do Rio Grande do Sul (1961) - Reis, Daniela Görgen dos (2012)
This dissertation aims problematizing how the State Government of Rio Grande do Sul through its press assessorship of Piratini Palace photos built the visuality of the movement of Legality. The documentary corpus is composed of 402 scanned negatives, among them were selected 100 images to be analyzed and interpreted. Throughout the work sought to understand the production of photographic images by the Executive power in political and social context of re-democratization of Brazil, from 1945 until 1961, as well as a new visual culture in the years 1950 (photo-journalism, illustrated magazines and television). It was noted that the growing interest of the political elite by the use of new media (especially of photography) to more effectively disseminate political advertising among the popular classes. The analysis of images through iconic descriptors (content), i.e. what appears in the photograph; along with formal descriptors (forms of expression), that realize how these elements appear in the photo, to interpret the forms of political representation of Governor Leonel Brizola and other leaders in the movement of Legality (1961).